Front Cover. Issue 12 (6th November 2019) - Boyé, Aurélien; Thiébaut, Éric; Grall, Jacques; Legendre, Pierre; Broudin, Caroline; Houbin, Céline; Le Garrec, Vincent; Maguer, Marion; Droual, Gabin; Gauthier, Olivier
Abstract : The cover image is based on the Original Article Trait‐based approach to monitoring marine benthic data along 500 km of coastline by Aurélien Boyé et al., https://doi.org/10.1111/ddi.12987 .